Website Users Satisfaction Study Among Students Bola.Net (Tunas University Students Study P.O.K Surakarta Force Development 2014) - Saputro, Wahyu Istiono, Agus Triyono, S.Sos, M.Si (2016)
Trasnformasi communications while experiencing very rapid and mass media are now more use of electronic and internet bebrbasis meruapakan information technology today is the website. The purpose of this study was to determine the satisfaction gap (Gratification Discrepancy) obtained by website users Bola.net the information needs among students POK University Surakarta Force Development Branch, 2014. This research is quantitative research with a comparative approach. The population in this study were students POK University Development Surakarta Tunas force in 2014, the study sample was 70 students POK University Development Surakarta Tunas force in 2014, with incidental sampling as a sampling technique, which is taking a chance. The technique of collecting data using questionnaires. Data analysis techniques in this study using gap analysis discrepancy. The results showed that: (1) The calculation motif use Bola.net website obtained the average value of the motif information, personal identity, integration and social interaction and entertainment motif is 3.16 which is in the interval from 3.01 to 4.00 with a percentage of 48%, so it can be seen that the desired satisfaction (gratification Sought) at the time before using the website Bola.net the information needs among students POK University Development Surakarta Tunas force in 2014 in the high category; (2) The calculation of satisfaction Bola.net website usage above the average values obtained from the satisfaction of information, personal identity, integration and social interaction and entertainment satisfaction is 3.10 which is in the interval from 3.01 to 4.00 with a large percentage of 67.5%, so it can be seen that the satisfaction derived (gratification Obatined) after using the website Bola.net the information needs among students POK University Development Surakarta Tunas force in 2014 in the high category; (3) Based on the above calculation can be seen that the average level of user satisfaction Website Bola.net gap was 1.7%, so that website users bola.net still was not satisfied with the services provided by the website manager bola.net. Gaps satisfaction (Gratification Discrepancy) obtained by website users Bola.net the information needs among students POK University Development Surakarta Tunas force in 2014 included in the low category with a percentage of between 20-30%.